A recombinant slow-release PACAP-derived peptide alleviates diabetes by promoting both insulin secretion and actions. (May 2015) - Ma, Yi; Fang, Shixiong; Zhao, Shaojun; Wang, Xiaoli; Wang, Dongbo; Ma, Min; Luo, Tianjie; Hong, An
Abstract: Pituitary adenylate cyclase activating polypeptide (PACAP) is a neuroendocrine factor that activates both the receptor VPAC1 and VPAC2. Although PACAP possesses insulinotropic activity, its therapeutic application is limited by the extremely short acting half-life and the stimulatory effects on glucagon production via a VPAC1-dependent mechanism. Here we have generated a recombinant PACAP-derived peptide (named as MHDBAY) comprising a 7-mer albumin-binding peptide identified by phage display screening (WQRPSSW), a cleavage peptide for Factor Xa (FXa) and dipeptidyl peptidase IV (DPP IV), and a 31-amino acid PACAP-derived peptide (DBAY) that can specifically bind to the VPAC2 receptor. MHDBAY binds to albumin both in vitro and in animals, thereby leading to an orderly slow release of the active peptide DBAY via the protease cleavage. In db/db mice and New Zealand rabbits, the circulating half-life of MHDBAY is approximately 12.2 h, which is 146-fold longer than DBAY (∼5 min). A single injection of MHDBAY into db / db diabetic mice markedly increases insulin secretion, thereby leading to sustained alleviation of hyperglycemia. The potency and duration of MHDBAY in increasing insulin secretion and decreasing blood glucose levels is much greater than Exendin-4, an anti-diabetic drug via its insulinotropic actions. Furthermore, chronic administration of MHDBAY by daily injection for 8 weeks significantly improves both glucose and lipid profiles and also greatly increases insulin sensitivity in db / db mice. These findings suggest that serum albumin may act as a reservoir for slow-release of small bioactive peptides, and MHDBAY may represent a promising therapeutic peptide for diabetes.